Study of growth and yield of several sources of indonesian konjac (Amorphophallus onchophyllus) seedling by CPPU treatments - Ramdan Hidayat (Future Science)
Indonesian konjac (Amorphophallus onchophyllus L.) are plants that contain high glucomannan substances and have distinctive growth characteristics that are influenced by weather changes. When entering the rainy season, the seeds grow and when they enter the dry season is dormancy, so the active growth period for konjac is only about 4 - 5 months. Seeds for cultivation of konjac, apart from being tubers, can also use bulbils or seeds. One of the efforts to promote the growth of konjac plants is the application of the growth regulator CPPU (N- (2-Chloro-4-pyridinyl) -N-phenylurea) as a cytokinin that effectively inhibits aging and accelerates cell division. The research objectives were to determine the interaction between the treatment of CPPU concentration and the kind seed source, to determine the effective concentration of CPPU and to determine the best type of seed source for konjac cultivation. The factorial experiment with two factors was arranged in a randomized block design (RBD) with 3 replications. The first factor in the treatment of CPPU concentration consisted of 4 levels (control, 5 ppm, 10 ppm and 15 ppm) and the second factor was the kind of seed source consisting of 3 types of seeds (tubers, bulbils and seeds). The results showed that there was no significant interaction of combination treatment of CPPU concentration and kinds of seed sources on the growth and yield of konjac plants. The concentration of growth regulators CPPU significantly affected tuber weight, increased tuber weight, tuber diameter and active growth period. The CPPU concentration of 15 ppm produced the highest weight of konjac tubers. The source of seedlings from bulbil is better than the source of seed from tubers and seeds in terms of increasing tuber weight.